Ascertainment of acute liver injury in two European primary care databases. - Ruigómez, A.; Brauer, R.; Rodríguez, L.; Huerta, C.; Requena, G.; Gil, M.; Abajo, Francisco; Downey, G.; Bate, A.; Tepie, M.; Groot, M.; Schlienger, R.; et al. (European Journal of Clinical Pharmacology, 2014)
Purpose: The purpose of this study was to ascertain acute liver injury (ALI) in primary care databases using different computer algorithms. The aim of this investigation was to study and compare the incidence of ALI in different primary care databases and using different definitions of ALI. Methods: The Clinical Practice Research Datalink (CPRD) in UK and the Spanish 'Base de datos para la Investigación Farmacoepidemiológica en Atención Primaria' (BIFAP) were used. Both are primary care databases from which we selected individuals of all ages registered between January 2004 and December 2009. We developed two case definitions of idiopathic ALI using computer algorithms: (i) restrictive definition (definite cases) and (ii) broad definition (definite and probable cases). Patients presenting prior liver conditions were excluded. Manual review of potential cases was performed to confirm diagnosis, in a sample in CPRD (21 %) and all potential cases in BIFAP. Incidence rates of ALI by age, sex and calendar year were calculated. Results: In BIFAP, all cases considered definite after manual review had been detected with the computer algorithm as potential cases, and none came from the non-cases group. The restrictive definition of ALI had a low sensitivity but a very high specificity (95 % in BIFAP) and showed higher rates of agreement between computer search and manual review compared to the broad definition. Higher incidence rates of definite ALI in 2008 were observed in BIFAP (3.01 (95 % confidence interval (CI) 2.13-4.25) per 100,000 person-years than CPRD (1.35 (95 % CI 1.03-1.78)). Conclusions: This study shows that it is feasible to identify ALI cases if restrictive selection criteria are used and the possibility to review additional information to rule out differential diagnoses. Our results confirm that idiopathic ALI is a very rare disease in the general population. Finally, the construction of a standard definition with predefined criteria facilitates the timely comparison across databases.